Petri Cantoris Parisiensis Verbum Adbreviatum: Textus prior and Textus alter. Edited by Monique Boutry - Ward, Benedicta (The journal of theological studies, 2013)
These two volumes provide a critical edition of the widely read texts of the Chanter (†1197), one of the most influential theologians in the exciting world of academic Paris in the late twelfth century. He saw the work of a theologian as composed of lecturing, disputing, and preaching, and all of his surviving work was meant to help others to use these methods. He was the first to compose lectiones on all the books of the Bible; his discussions of the sacraments were collected in a large Summa de Sacramentis.